Low Understanding of Mathematical Concepts and Local Culture: A Case Study of Elementary School Students in Tanah Laut Regency - Alya Farhana Maulida; Anik Ghufron (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2026)
Abstract: This research aims to identify the level of students' understanding of mathematical concepts and mastery of local culture as a basis for the development of a local culture-based learning model, as well as to determine the factors causing the low level of understanding of concepts and lack of local culture in mathematics learning. This research employs a mixed-method approach with a quantitative design supplemented by qualitative data. The subjects include 24 fifth-grade students at an elementary school in Tanah Laut Regency. Data collection techniques include mathematics concept comprehension tests, local cultural understanding tests, and documentation. The results showed that only 20.83% of students achieved a high category in understanding two-dimensional shapes, while understanding of local culture was very low only 4.167% of students able to identify cultural elements accurately. The implications of this study suggest that contextual teaching materials based on local culture need to be developed to help students better understand mathematical concepts while fostering a love for their own culture. Abstrak: Penelitian ini mengidentifikasi tingkat pemahaman konsep matematika dan penguasaan budaya lokal sebagai dasar pengembangan model pembelajaran berbasis budaya lokal serta untuk mengetahui penyebab rendahnya pemahaman konsep dan kurangnya budaya lokal dalam pembelajaran matematika. Penelitian ini menggunakan metode mixed-method dengan desain kuantitatif yang diperkuat data kualitatif. Subjek 24 siswa kelas V di sebuah sekolah dasar di Kabupaten Tanah Laut. Teknik pengumpulan data meliputi tes pemahaman konsep matematika, tes pemahaman budaya lokal, dan dokumentasi. Hasil penelitian menunjukkan hanya 20,83% siswa yang mencapai kategori tinggi dalam pemahaman konsep bangun datar, sementara pemahaman terhadap budaya lokal sangat rendah yaitu 4,167% siswa mampu mengidentifikasi unsur budaya secara tepat. Hasil ini menunjukkan perlu dikembangkan bahan ajar kontekstual berbasis budaya lokal agar siswa lebih mudah memahami konsep matematika sekaligus menumbuhkan kecintaan pada budaya sendiri.